Measuring indoor fine particle concentrations, emission rates, and decay rates from cannabis use in a residence. (April 2021) - Ott, Wayne R.; Zhao, Tongke; Cheng, Kai-Chung; Wallace, Lance A.; Hildemann, Lynn M.
Abstract: Fifteen states have legalized the sales of recreational marijuana, and California has the largest sales of any state. Cannabis is most often smoked indoors, but few measurements have been made of fine particle mass concentrations produced by secondhand cannabis smoke in indoor settings. We conducted 60 controlled experiments in a 43 m 3 room of a residence, measuring PM2.5 concentrations, emission rates, and decay rates using real-time monitors designed to measure PM2.5 mass concentrations. We also measured the room's air exchange rate. During each experiment, an experienced smoker followed an identical puffing protocol on one of four different methods of consuming marijuana: the pre-rolled marijuana joint (24 experiments), the bong with its bowl containing marijuana buds (9 experiments), the glass pipe containing marijuana buds (9 experiments), and the commercially available electronic vaping pen with a cartridge attached containing cannabis vape liquid (9 experiments). For comparison, we used the same puffing protocol to measure the PM2.5 emissions from Marlboro cigarettes (9 experiments). The results indicated that cannabis joints produced the highest indoor PM2.5 concentrations and had the largest emission rates, compared with the other cannabis sources. The average PM2.5 emission rate of the 24 cannabis joints (7.8 mg/min) was 3.5 times the average emission rate of the Marlboro cigarettes (2.2 mg/min). The average emission rate of the cannabis bong was 67% that of the joint; the glass pipe's emission rate was 54% that of the joint, and the vaping pen's emission rate was 44% that of the joint. The differences compared to the joint were statistically significant. Highlights: 60 experiments comparing indoor PM2.5 from secondhand marijuana & tobacco smoke. The marijuana joint's emission rate was 3.5 times that of the tobacco cigarette. All the cannabis sources had PM2.5 emission rates greater than tobacco cigarettes. The order of cannabis emission rates was joint, bong, glass pipe, and vaping pen. The vaping pen's mean decay rate exceeded the other sources' mean decay rates.